The Heterothrips species of Argentina, with two new species and biological notes (Thysanoptera, Heterothripidae) - de Borbón, Carlos Manuel (Zootaxa, 2010)
Two new species of Heterothrips are described from Mendoza, Argentina: H. pilarae from flowers of Tricomaria usillo (Malpighiaceae), and H. stellae from Prosopis alpataco (Fabaceae). These species share several morphological characters with H. araucaniae and H. johanseni from Chile. A key is provided to species of Heterothrips from Argentina, with notes on the biology of some species.